THE DIFFERENCES OF HEAD SHAPE CHARACTERISTICS IN KALIMANTAN TRIBES USING FRONTOPARIETAL INDEX - Zahroh, Khanifatu; DH, Irnamanda; Aflanie, Iwan (FKG Unlam, 2018)
Backgrounds: Kalimantan is the largest island in Indonesia that consists of 5 provinces, including South Kalimantan and Central Kalimantan. South Kalimantan and Central Kalimantan are inhabited by several tribes such as Dayak Bukit tribe, Banjar Hulu tribe and DayakNgajutribe. The geographic condition of inter-ethnic residence affects the phenotype pattern that will characterize each population. Those characteristics can be measured using the frontoparietal index that are classified into 3 characteristic forms, which are <68.9% (Sthenomethopia/narrow forehead), 69.0-70.9% (Metriometopia/moderate forehead) and >71,0 (eurymetopia/wide forehead). Objective: To know the difference in head shape characteristicsusing frontoparietal index betweenDayak Bukit tribe, Banjar Hulu tribe and DayakNgaju tribe. Methods: This research was an analytic observational study with cross sectional design,using 180 people that consisted of 60 people from Dayak Bukit tribe, 60 people from DayakNgaju tribe, and 60 people from Banjar Hulu tribe which were measured by using digital caliper. Results: Measurements showed that the mean of frontoparietal index were 89,20% (Eurymetopia) in Dayak Bukit tribe, 88,77% (Eurymetopia) in BanjarHulu tribe, and 89,63% (Eurymetopia) in DayakNgaju tribe. The results of the research analyzed by Chi Square test with p=0,36 (p>0,05). ItÂ showed thatthere was no difference in head shape characteristics using frontoparietal index between Dayak Bukit tribe, Banjar Hulu tribe and DayakNgaju tribe. Conclusion: Frontoparietal index can not be used to differentiate the head shape characteristics of Dayak Bukit tribe, Banjar Hulu tribe and DayakNgaju tribe.